STUDIES ON THE FISHERY AND BIOLOGY OF THE COMMERCIAL CAT-FISHES OF THE GANGA RIVER SYSTEM I. Eirly Life-History, Bionomics and Breeding of Mystus (Osteobagrus) seenghala (Syke - Saigal, B N; Motwani, M P (Indian Journal of Fisheries, 2011)
The two species of Gangetic tengra, Mystus (Osteobagrus) aor (Hamilton)and Mystus Osteobagrus) seenghala (Sykes) are widely distributed of thefreshwater species of cat-fishes in India, occurring in almost all the principalriver systems of India, Pakistan and Burma. In the Ganga River system,the two species constitute fishery of considerable commercial importancethroughout the year and data relating to commercial landings over a numberof years, reveal that their fishery ranks next only to that of Hilsa ilisha (Hamilton)and Cirrhinus mrigala (Hamilton